Conceptual negativism in Chipewyan ethnology - Koolage, William W. Jr. (2012)
This paper attempts to elucidate how the concept and/or labels of deculturation, disorganization, and disintegration have been employed by anthropologists and Canadian Government researchers in their appraisals of the Chipewyan culture and society, and make some inferences as to why they have been utilized. Assuming the anthropologists described what they observed, why did they see the Chipewyan as they did?